2014
DOI: 10.1126/scitranslmed.3007901
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in CSF Biomarkers in Autosomal-Dominant Alzheimer’s Disease

Abstract: Clinicopathologic evidence suggests the pathology of Alzheimer disease (AD) begins many years prior to cognitive symptoms. Biomarkers are required to identify affected individuals during this asymptomatic (“pre-clinical”) stage to permit intervention with potential disease-modifying therapies designed to preserve normal brain function. Studies of families with autosomal-dominant AD (ADAD) mutations provide a unique and powerful means to investigate AD biomarker changes during the asymptomatic period. In this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
289
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 349 publications
(329 citation statements)
references
References 100 publications
35
289
2
3
Order By: Relevance
“…In both symptomatic and presymptomatic APP , PSEN1 and PSEN2 mutation carriers, the majority of the studies found a decrease in Aβ 42 and an increase in both t-tau and p-tau levels when compared with healthy control individuals, consistent with a typical AD profile [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] (table 1). In some cases, 1 or more markers were found to be unchanged compared to controls [27,28,29,30].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In both symptomatic and presymptomatic APP , PSEN1 and PSEN2 mutation carriers, the majority of the studies found a decrease in Aβ 42 and an increase in both t-tau and p-tau levels when compared with healthy control individuals, consistent with a typical AD profile [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] (table 1). In some cases, 1 or more markers were found to be unchanged compared to controls [27,28,29,30].…”
Section: Resultsmentioning
confidence: 93%
“…In individuals carrying APP or PSEN1 mutations, levels of F2-isoprostanes, which are markers of lipid peroxidation, were found to be elevated compared with controls [20]. In another study, a marker of neuronal death, VILIP-1, was found to be increased in carriers of APP , PSEN1 and PSEN2 mutations [13]. In 3 studies, mass spectrometry was used to assess Aβ isoforms and the proteome in familial AD [9,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…The stability of our markers in this early stage of motor PD could result from a slowing of the neurodegeneration process in the symptomatic phase similar to that seen in AD. 32 This underlines the need for more specific progression marker candidates for the early phase of the disease, which will emerge from this and other ongoing studies. 33 We explored many obvious candidates in a large cohort of PD participants and looked for progression markers for future use in clinical trial cohorts and tried to exclude noninformative ones.…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing number of longitudinal studies in asymptomatic subjects with or at risk for AD by virtue of a mutation (25,26), gene status (27,28), or significant amyloid burden as measured by PET (29,30) or cerebrospinal fluid analyses (31). Although highly interesting from the perspective of clinical trials, we did not include asymptomatic individuals in the present study, because their clinical fate is unclear.…”
Section: Discussionmentioning
confidence: 99%